1993
DOI: 10.2330/joralbiosci1965.35.312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the texture of food on the masticatory process.

Abstract: The mode of mastication of soft foods was examined through visual analysis with cineradiography and self description by experimental subjects, using agar and gelatin gels as test foods. The mode altered from compression with the tongue and hard palate to shearing with the dentition as the hardness of model samples was increased. The thresholds of hardness requiring a shift of mastication mode from compression to shearing were 0 .08 kg for the agar gel and 0.03 kg for the gelatin gel, although the gelatin gel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…The compressive force at over 80% strain may be related to a resistance to completely cut off cooked wheat noodles (Sasaki et al, 2004). Compressive force at slight deformation may be related to the initial perception of the palate (Sherman, 1969;Arai and Yamada, 1993;Sasaki et al, 2004). In our experiment, the differences in compressive force among buckwheat fl ours were clear at 80 and 90% strains, when noodle strands were cut largely, although the differences were not detected at a strain of 40% or less, when noodle strands were cut slightly.…”
Section: Discussionmentioning
confidence: 56%
“…The compressive force at over 80% strain may be related to a resistance to completely cut off cooked wheat noodles (Sasaki et al, 2004). Compressive force at slight deformation may be related to the initial perception of the palate (Sherman, 1969;Arai and Yamada, 1993;Sasaki et al, 2004). In our experiment, the differences in compressive force among buckwheat fl ours were clear at 80 and 90% strains, when noodle strands were cut largely, although the differences were not detected at a strain of 40% or less, when noodle strands were cut slightly.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the selection criteria for the shape of the denture’s palatal surfaces are vague, with shape selection dependent on the dentist’s clinical experience alone. It has been reported that humans perceive food by pressing it against the palate with the tongue during food ingestion (8). Therefore, covering the palate with dentures influences the perception of food texture.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid foods are swallowed instantaneously, and the solid foods are masticated and made into a bolus before being swallowed. These processes can be visualized by videofluorography [107,108]. 3.…”
Section: Location Of Foods or Tongue Movementmentioning
confidence: 99%